PENGARUH PROFITABILITAS DAN BEBAN PAJAK PENGHASILAN KINI TERHADAP KEPUTUSAN PENDANAAN DENGAN PERTUMBUHAN PERUSAHAAN SEBAGAI PEMEDIASI PADA PERUSAHAAN DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Agnes Puji Christiani; Susi Dwimulyani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The purpose of this study was to examine the effect of profitability, current income tax burden, company growth on funding decisions. Another goal is to test the growth of the company as a mediator in the relationship between profitability and funding decisions and the current income tax burden with funding decisions. The research data was obtained from the company's annual report from the Indonesia Stock Exchange (IDX) website. The sample used as many as 20 property companies listed on the Stock Exchange in 2012-2016. The sampling technique uses purposive sampling. This study uses the method of multiple regression analysis and path analysis. Based on the results of the analysis it was concluded that profitability had a significant positive effect on the growth of the company. Income tax expense has a significant positive effect on company growth. The company's growth has a significant positive influence on funding decisions. Profitability does not affect funding decisions. The current income tax expense has no effect on funding decisions. Profitability through company growth variables has a significant effect on funding decisions. Current income tax expense through company growth variables has a significant effect on funding decisions.